Foreign Capital Inflows and Stock Market Development in Nigeria: An Asymmetric Causality Approach - Emmanuel Olayemi Awoleye (Faculty of Economic and Business Syarif Hidayatullah State Islamic University of Jakarta, 2022)
The study used the recently developed symmetric and asymmetric Granger causality test by Hatemi-J to investigate the causal relationships between foreign capital inflows and stock market development in Nigeria from 1986 to 2019. The findings show unidirectional symmetric causality between stock market development and foreign direct investment, while no symmetric causality was found between stock market development and foreign portfolio investment. The results show unidirectional asymmetric causality of positive and negative shocks of stock market development to the negative shock of foreign direct investment. In contrast, the negative shock of stock market development shows a unidirectional asymmetric causality to the positive shock of foreign portfolio investment. The results revealed the causality relationship between foreign capital inflows and stock market development, including positive and negative aspects in Nigeria. These findings have implications for portfolio design and strategies that are important to policymakers and investors.How to Cite:Awoleye, E. O., (2022). Foreign Capital Inflows and Stock Market Development in Nigeria: An Asymmetric Causality Approach. Signifikan: Jurnal Ilmu Ekonomi, 11(2), 339-354. https://doi.org/10.15408/sjie.v11i2.26195.JEL Classification: G12, F21, D82, C19